The polyadenylation site of Mimivirus transcripts obeys a stringent ‘hairpin rule’ - Byrne, Deborah; Grzela, Renata; Lartigue, Audrey; Audic, Stéphane; Chenivesse, Sabine; Encinas, Stéphanie; Claverie, Jean-Michel; Abergel, Chantal (Genome Research, 2009)
Mimivirus, a giant DNA virus infecting Acanthamoeba, is revealing an increasing list of unique features such as a 1.2-Mb genome with numerous genes not found in other viruses, a uniquely conserved promoter signal, and a particle of unmatched complexity using two distinct portals for genome delivery and packaging. Herein, we contribute a further Mimivirus distinctive feature discovered by sequencing a panel of viral cDNAs produced for probing the structure of Mimivirus transcripts. All Mimivirus mRNAs are polyadenylated at a site coinciding exactly with unrelated, but strongly palindromic, genomic sequences. The analysis of 454 Life Sciences (Roche) FLX cDNA tags (150,651) confirmed this finding for all Mimivirus genes independent of their transcription timings and expression levels. The absence of a suitable palindromic signal between adjacent genes results in transcripts encompassing multiple ORFs in the same or even in opposite orientations. Surprisingly, Mimivirus tRNAs are expressed as polyadenylated messengers, including an ORF/tRNA composite mRNA. To our knowledge, both the nature and the stringency of the “hairpin rule” defining the location of polyadenylation sites are unique, raising once more the question of Mimivirus's evolutionary origin. The precise molecular mechanisms implementing the hairpin rule into the 3′-end processing of Mimivirus pre-mRNAs remain to be elucidated.
10.1101/gr.091561.109